Myositis-specific antibodies in dermatomyositis: A single-center experience of 33 cases in Taiwan - Wei-Ting Liu; Chao-Chun Yang (Wolters Kluwer Medknow Publications, 2023)
Dermatomyositis (DM) is a systemic autoimmune disease characterized by unique cutaneous manifestations and inflammatory myopathies. With the discovery of myositis-specific antibodies (MSAs), patients with DM, especially those with a higher risk of life-threatening complications, can be classified according to the MSA type. This retrospective study aimed to investigate the clinical significance of MSAs in patients with DM in Taiwan. A total of 33 patients with DM who underwent the MSA test, including 26 with classic DM and 7 with amyopathic DM, were included. There were 13 men and 20 women, with a mean age at diagnosis of 49.6 years. MSA was detected in 26 (78.8%) of 33 patients with DM. The most frequently detected MSA was anti-melanoma differentiation-associated protein 5 (MDA5) (10/33, 30.3%) followed by anti-transcription intermediary factor-1γ (TIF-1γ) (8/33, 24.2%). Dysphagia was present in 6 (18.2%) of the 33 patients and more frequently developed in patients with anti-TIF-1γ (+) (5/8, 62.5%) than those with anti-TIF-1γ (−) (1/25, 4.0%). Interstitial lung disease was noted in 15 patients (45.5%) and developed more frequently in patients with anti-MDA5 (+) (7/10, 70.0%) than those with anti-MDA5 (−) (8/23, 34.8%). Malignancies were detected in 4 (12.1%) patients, with one each of anti-Mi-2 (+), anti-TIF-1γ (+), anti-ARS (+), and MSA (−). Mortality occurred in 6 (18.2%) patients, of whom 4 were anti-MDA5 (+). Anti-MDA5 and anti-TIF-1γ were the two most commonly detected MSAs. The presence of specific MSAs is associated with a certain phenotype, and integrating MSAs while evaluating DM aids in accurate patient management.